2018
DOI: 10.1039/c8re00049b
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Boscalidviaa three-step telescoped continuous flow process implemented on a MJOD reactor platform

Abstract: A three step continuous/semi-flow process leading to the fungicide Boscalid® is disclosed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…In the patented route by the BASF, although complete details about the process are lacking, the sequence involved (1) a Pd(0)-catalyzed Suzuki–Miyaura (SM) coupling, (2) reduction of the nitrobiaryl intermediate, and (3) an amide bond construction. A few new routes have appeared recently, including one utilizing flow chemistry; however, all involve use of organic solvents, high catalyst loadings, and especially high temperatures. Moreover, selective nitro group reduction in the presence of an aryl chloride required expensive Pt/C under high pressure of hydrogen. , Dunst and Knochel used an alternative approach to replace the Suzuki–Miyaura (SM) reaction by a Kumada-type coupling leading to the desired biarylamine in 70% yield with 1 mol % of a Pd catalyst .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the patented route by the BASF, although complete details about the process are lacking, the sequence involved (1) a Pd(0)-catalyzed Suzuki–Miyaura (SM) coupling, (2) reduction of the nitrobiaryl intermediate, and (3) an amide bond construction. A few new routes have appeared recently, including one utilizing flow chemistry; however, all involve use of organic solvents, high catalyst loadings, and especially high temperatures. Moreover, selective nitro group reduction in the presence of an aryl chloride required expensive Pt/C under high pressure of hydrogen. , Dunst and Knochel used an alternative approach to replace the Suzuki–Miyaura (SM) reaction by a Kumada-type coupling leading to the desired biarylamine in 70% yield with 1 mol % of a Pd catalyst .…”
Section: Introductionmentioning
confidence: 99%
“…A few new routes have appeared recently, including one utilizing flow chemistry; however, all involve use of organic solvents, high catalyst loadings, and especially high temperatures. Moreover, selective nitro group reduction in the presence of an aryl chloride required expensive Pt/C under high pressure of hydrogen. , Dunst and Knochel used an alternative approach to replace the Suzuki–Miyaura (SM) reaction by a Kumada-type coupling leading to the desired biarylamine in 70% yield with 1 mol % of a Pd catalyst . In short, none of these methods offer an environmentally sustainable, benign approach.…”
Section: Introductionmentioning
confidence: 99%
“…Schwarze et al 15 reported an environmentally friendly solvents for synthesis of Boscalid, the Suzuki reaction was catalyzed by watersoluble homogeneous Pd/SPhos, together with an easily recyclable heterogeneous PtIr@TiO 2 , the condensation reaction under the conditions of triethylamine, the catalysts used are not easily available. Audun Drageset et al 16 reported a three step continuous/semi-flow process for synthesis of Boscalid, the Suzuki coupling reaction was catalyzed by Pd(PPh 3 ) 4 , the reduction reaction was used of NaBH 4 /CoSO 4 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, using a similar reaction sequence adapted to run on a multijet oscillating disk (MJOD) continuous flow reactor platform, a group at the University of Bergen in Norway reported the production of boscalid at a rate of around 8.4 g/h in 42% overall yield for the three steps. 23 In that route, a lowertemperature (80 °C) Suzuki−Miyaura coupling was used, which was followed by a cobalt boride reduction step to efficiently convert the nitro group to the required amine substituent. The final coupling was achieved through the in situ formation of an iminosulfanone using SOCl 2 followed by condensation with 2-chloropyridine-3-carboxylic acid.…”
Section: The Agrochemical Industrymentioning
confidence: 99%